The DMA, TG/DTA and FT-IR Characteristics of Wood Polymer Composites - Koyun, Ahmet; Ahlatcioglu, Esma; Erdogan, Duygu Ceylan; Ipek, Yeliz Koca (TRANS TECH PUBLICATIONS LTD, 2012)
Wood chips and polymer composites are effectively used in the industrial products. It is important to establish a relationship between mechanical strength and processability in extruder of these composites. Especially, the most important factor is to determine the time-dependent strength. Although many short-term values were obtained via normal mechanical experiments, very little effort has been spent in order to estimate the long-term behavior of polymer. Composites were prepared with processed and unprocessed wood chips. Pretreatment of wood chips were carried out by using hydrochloric acid (HCl) and water. The products were prepared with different ratios of mixtures which contain wood chips and high density polyethylene (HDPE) grains. The long-term mechanical behavior and viscoelastic behavior of these composites were analyzed using Dynamic Mechanic Analyzer (DMA) test equipment. The effect of composite content and pretreatment method of wood chips on mechanical strength of wood plastic composites (WPCs) were determined. The relationship among the composite content, preparation method of wood chips, DMA and TG/DTA test results were tried to establish. FT-IR spectrums of the beginning materials and the composites are also examined in order to determine the chemical bonds of these materials.
Keywords: Wood Polymer Composites; Processed wood chips; DMA; TG/DTA; FT-IR; Lignocellulosic Material; Engineering; Materials Science